(untitled) (Bangladesh Journal of Medical Science, 2014)
Background: Geographically Kashmir valley is isolated from the rest of the country. It has a different climate with people having different social and dietary habits. Gastric cancer, esophageal, and skin (Kangri) cancer have a higher prevalence but there is little data available on the cancers of brain. Objectives & Methodology: Aim was to study brain tumors prospectively and retrospectively, to analyse brain tumors geographically and to analyse the age and sex ratio of brain tumors in Kashmir valley. In this Retrospective and Prospective study, retrospectively (initial seven years) all patients were analyzed for their clinical symptoms, age, sex, residence, histopathologic characteristics of tumors. Prospectively (later three years) after get-ting the radiological diagnosis pathological diagnosis was arrived by procedures like open, stereotactic, and endoscopic procedures. All patients were then analysed for age, sex, residence, signs and symptoms and histopathological characteristics. Follow up was done for gliomas. Mortality and morbidity was analysed for gliomas in these 3 years. Patients who lost the follow up were considered dead. Out of 1730 patients included in our study, there were 1031 males and 699 females. The most common age group was between 41-50 years. Results: The most common tumor was gliomas followed by meningiomas. Gliomas were most common in men and meningiomas in females. Out of all the histological grades in gliomas, the glioblastoma multiforme (GBM) was the most common, and frontal lobe was the commonest anatomical site involved. The most common symptom in our study was headache followed by vomiting. DOI: http://dx.doi.org/10.3329/bjms.v13i3.19148 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.268-277